Bacterial diversity in organic and conventional Minas Frescal cheese production using targeted 16S rRNA sequencing - Abreu, Anderson Clayton da Silva; Carazzolle, Marcelo Falsarella; Crippa, Bruna Lourenço; Barboza, Giovana Rueda; Mores Rall, Vera Lúcia [UNESP]; de Oliveira Rocha, Liliana; Silva, Nathália Cristina Cirone (Elsevier, 2021)
Molecular identification and the study of bacteria in processed food products can be challenging or suffer limitations when using conventional methods. However, with Next Generation Sequencing (NGS), one can identify bacterial species with a significantly higher detection sensitivity using a 16S rRNA target gene. This study aimed to characterise the bacterial diversity of the organic and conventional production of Minas Frescal cheese, through the NGS analysis of the 16S rRNA gene. DNA was extracted from 96 samples, 48 from organic production and 48 from conventional production. The bacterial families and genera with the highest prevalence were identified. The most prevalent families were Enterobacteriaceae, Planococcaceae and Moraxellaceae. The NGS 16S rRNA tool proved to be very useful for bacterial characterisation, but it is still not possible to say whether a product contains more or less bacteria based on organic production, as there are several factors that contribute to contamination.